2020
DOI: 10.1007/s13369-020-04792-0
|View full text |Cite
|
Sign up to set email alerts
|

A SIR-Poisson Model for COVID-19: Evolution and Transmission Inference in the Maghreb Central Regions

Abstract: 2019-nCoV is a virulent virus belonging to the coronavirus family that caused the new pneumonia (COVID-19) which has spread internationally very rapidly and has become pandemic. In this research paper, we set forward a statistical model called SIR-Poisson that predicts the evolution and the global spread of infectious diseases. The proposed SIR-Poisson model is able to predict the range of the infected cases in a future period. More precisely, it is used to infer the transmission of the COVID-19 in the three M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…The scholarly literature on the effects of the COVID-19 pandemic on food systems and consumption patterns has been so far mostly geographically biased; it focuses on Western and Southern Europe, North America, and China (30), while developing countries in general and those of the NENA region in particular, such as Morocco, have been overlooked. The analysis of the scholarly literature shows that most of the papers dealing with the COVID-19 emergency in Morocco focus on the dynamics of the spread of the virus as well as its health impacts (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). Other articles analyze the pandemic's socio-economic impacts in the kingdom (45,59).…”
Section: Introductionmentioning
confidence: 99%
“…The scholarly literature on the effects of the COVID-19 pandemic on food systems and consumption patterns has been so far mostly geographically biased; it focuses on Western and Southern Europe, North America, and China (30), while developing countries in general and those of the NENA region in particular, such as Morocco, have been overlooked. The analysis of the scholarly literature shows that most of the papers dealing with the COVID-19 emergency in Morocco focus on the dynamics of the spread of the virus as well as its health impacts (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). Other articles analyze the pandemic's socio-economic impacts in the kingdom (45,59).…”
Section: Introductionmentioning
confidence: 99%
“…Let denote the number of infected cases in state r at time point t with . Usually, is assumed to follow a Poisson distribution [ 22 , 23 , 24 ]. Since the number of infected cases in each state is hardly totally observed (i.e., the existence of heterogeneity for different states), employing the Poisson assumption could underestimate the underlying dispersion.…”
Section: Development Of the Modelmentioning
confidence: 99%
“…Epidemiological studies have established prediction models based on existing data (Zhou et al 2020 ) and have identified the phenomenon of human transmission in China (Riou and Althaus 2020 ). Hassen et al ( 2021 ) proposed a susceptible–infectious–removed (SIR)–Poisson model to predict the range of future infections. Hoch et al ( 2018 ), meanwhile, established a susceptible–infectious–removed–susceptible (SIRS) model to simulate dynamic infection in a multigroup system.…”
Section: Introductionmentioning
confidence: 99%